Development of Hand Tracking and Hand Recognition for Virtual Manufacturing - Kiswanto, Gandjar; Rakhmat Ramadhan, Dody; Ayu Setiani, Adjeng; Zhultriz, Ferdiansyah; Fathin Juzar, Muhammad; Muhammad Suryantoro, Rachmad (International Journal of Engineering and Technology, 2018)
Development of information and technology very rapidly encourage people to create a simulation system. This simulation system can be used to simulate the manufacturing field. To make this simulation become more naturally it is used hand tracking and hand recognition as input device. This paper discusses the implementation background subtraction, CAMSHIFT and convex hull algorithms for Hand Tracking and Hand Recognition. Input given in the form of palm coordinates then the system will do the tracking by creating boundaries rectangle. Then separated between the hand image and the background on the boundaries. After that done calculate image processing to determine the pose of the hand. The result of this research is a system that will perform tracking and recognition and then the result next stage to be simulated
Keywords: Simulation; Background Subtraction; CAMSHIFT; convex hull; virtual manufacturing